If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6q + -3p = p + q Reorder the terms: -3p + 6q = p + q Solving -3p + 6q = p + q Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -3p + -1p + 6q = p + -1p + q Combine like terms: -3p + -1p = -4p -4p + 6q = p + -1p + q Combine like terms: p + -1p = 0 -4p + 6q = 0 + q -4p + 6q = q Add '-6q' to each side of the equation. -4p + 6q + -6q = q + -6q Combine like terms: 6q + -6q = 0 -4p + 0 = q + -6q -4p = q + -6q Combine like terms: q + -6q = -5q -4p = -5q Divide each side by '-4'. p = 1.25q Simplifying p = 1.25q
| y/8=y/5-4/5 | | 6=-5x+7 | | 3x+-y=22 | | 2x+20-y= | | x^8-y^8= | | 34-y=y+6 | | 129x^4+33ax^2+9a= | | x^(7/2)=51,4 | | 3(6+5x)=18 | | -3(3p+2)-2(5-8p)=3(7+2p) | | 4x-(-3)(-2)=18 | | 4x-16=3x-1.9 | | 4x(-3)(-2)=18 | | 2(6+x)=32 | | -12h-2(2h-6)=-36 | | 3y^4+6y^3+3y^2=0 | | c-62=812 | | 5xy-10x= | | 9x^4+9x^3y-x^2-xy= | | 7m=147 | | 11-(k+3k)=43 | | 1/3,1/4,1/5,1/6= | | 2y-1/3=x | | 42=5v+2 | | 7x-12=8x+3 | | 15y-18=20 | | -18=r-1 | | 3p-1/2)-(p/2-3/2)4-p/2 | | 42=2x-19 | | 16x^4-8x^2y^2-xy= | | -2=-4+n | | 2t+2=t+16 |